MERCOSUR, 25 ans plus tard : les problèmes structurels et les impacts du changement de conjoncture - Charles Pennaforte; Marcos Antônio Fávaro Martins (L'Espace Politique)
Our objective will be to analyses the progress of the process of institutionalization of MERCOSUL, in an effort to identify weaknesses and gaps to be filled. For that, we compare the current events of the domestic conjuncture of the States that are part with the qualified opinions about the construction of the “bloc”. We conclude that the bureaucratic sectors need improvement and reformation. We also affirm here that the defection block Venezuela more as a result of the changing political environment than a product of the inadequacies of that country to the bloc's standards, as suggested by the mass media.